Quantification of the ecosystem carrying capacity on China's Loess Plateau. (June 2019) - Liang, Wei; Fu, Bojie; Wang, Shuai; Zhang, Weibin; Jin, Zhao; Feng, Xiaoming; Yan, Jianwu; Liu, Yu; Zhou, Sha
Highlights: We analyze the spatiotemporal pattern of the ECC on the Loess Plateau. The average annual ECC is 577 ± 124 g C m −2 yr −1 during 1982–2012. Due to revegetation, 26 counties have exceeded the ECC threshold. 138 counties have water competition between ecosystems and socio-economic systems. Under future climate change and growing water demand, ECC will increase by 6–36%. Abstract: Revegetation, especially afforestation, has served as an important tool for controlling desertification. However, revegetation in water-limited regions will inevitably reduce the water available for socio-economic systems, which is poorly considered in decision-making on sustainable ecosystem management. This paper proposed a framework to determine the threshold of vegetation productivity (i.e., ecosystem carrying capacity), corresponding to available water resources for ecosystems (i.e., annual precipitation minus water demand for socio-economic systems) on the Loess Plateau. The average annual ecosystem carrying capacity (ECC) during 1982–2012 is 577 ± 124 g C m −2 yr −1, with spatial gradients increasing from northwest to southeast. Vegetation in rocky mountain areas has the largest value of 833 ± 200 g C m −2 yr −1 . Factorial analysis suggests that changes in precipitation and human water use contributed to 55% and 45% of the multi-decadal changes in regional ECC, respectively. Meanwhile, due to revegetation, 26 counties on the Loess Plateau, mainly in the southeast and eastern parts, have exceeded the ECC threshold during the study period. An additional 138 counties have a high potential for water competition between the ecosystems and socio-economic systems. At the regional scale, there are 9 years (∼30% of the study period) during which the ECC threshold has been exceeded, especially after 1997. Considering the climate change in the future and the growing demand for water in socio-economic systems, the corresponding ECC threshold will increase by 6–36%. We believe that these findings can provide reference for policy-makers to make decisions towards ecosystem sustainability while meeting human needs for water resources.